PENGARUH PROFITABILITAS, ENVIRONMENTAL MANAGEMENT SYSTEM, KEPEMILIKAN INSTITUSIONAL DAN KOMITE AUDIT TERHADAP CARBON EMISSIONS DISCLOSURE - Yenty Suherman; Kurniawati Kurniawati (Program Studi Diploma III Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mataram, 2023)
This study aims to analyze the effect of profitability, environmental management systems, institutional ownership, and audit committees on carbon emission disclosure. The research population is energy companies registered on the Indonesia Stock Exchange in 2019-2021. The sample selection used a purposive sampling technique and resulted in 47 companies as the final sample. The results of this study show that the environmental management system and audit committee significantly affect carbon emission disclosure. In contrast, profitability and institutional ownership do not significantly affect carbon emission disclosure.